Elements of fiction - Mosley, Walter (Grove Press, 2019)
"In his essential writing guide, This Year You Write Your Novel, Walter Mosley supplied aspiring writers with the basic tools and practical advice needed to write a novel in a single year. In this complementary follow up, Mosley guides the reader through the fundamental building blocks of fiction to deliver a master class on the writer's craft. In a series of conversational and instructive chapters, Mosley breaks down the art of fiction to its most essential elements: character and character development, plot and story, voice and narrative, context and description. The result is a detailed depiction of the writing process, from the blank page to the first draft to rewriting, and rewriting again. Throughout, Elements of Fiction is enriched by the author's reflection on his own methods and enlivened by engaging demonstrative examples, not drawn from other literary works but written by Mosley himself. Inspiring, accessible, and told in a voice both trustworthy and wise, Elements of Fiction is an indispensable book of tips, tools, and advice for writers and readers alike"--